Decision Support System for Teacher Performance Assessment at SMP Negeri 1 Talang Padang Using the Weight Product Method - Desi Tosary; Maryaningsih Maryaningsih; Lena Elfianty (Jurnal Komputer, Informasi dan Teknologi, 2021)
Teacher performance assessment aims to improve the quality of teaching and learning activities. The obstacle faced is the difficulty of evaluating teacher performance objectively due to the many responsibilities of teachers to students and to schools. To overcome these obstacles, a decision support system with the Weight Product method is needed to be used as a tool to support the decision-making process. The Weight Product method uses multiplication to connect attribute ratings, where the rating of each attribute is raised first to the weight of the attribute in question. The implementation of the system uses the Visual Basic 2010 programming language and the method used in this study is the waterfall method. From the results of the tests carried out, it can be concluded that the teacher performance assessment using the Weight Product can be done well by taking the top number of teachers from the Weight Product ranking process which can then be reported in the form of a teacher performance assessment report.